Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pasien di Rumah Sakit Gigi dan Mulut Universitas Jember - Surartono Dwiatmoko (Faculty of Dentistry, Universitas Indonesia, 2015)
The quality of health service can be viewed from the sides of the health service provider such as hospital or health service center, and the patient as the service user. The quality of service according to the patient is reflected in the patient satisfaction. The patient satisfaction is essential information for hospital or other health service center to design strategy to improve performance for survival under strict competition. The purpose of this research was to determine the influcence of the service quality according to the patient, in terms of tangibility, reliability, responsiveness, assurance and empathy, on patient satisfaction. The research was conducted at Dental Hospital, University of Jember from September 2005 to February 2006. The research was applied to the multi-visit patients, who were handled by professional level students. This observational research was carried out by using cross sectional approach, in which data was collected using questionnaire. The sample included 150 people, and the data were subsequently analyzed using double regression analysis on the influence of the service quality toward patient satisfaction. The results showed that tangibility, reliability, responsiveness, assurance and empathy factors simultaneously influence the patient satisfaction with R2 value of 0.809. The partial correlation coefficients were tangibility 0.198, reliability 0.207, responsiveness 0.197, assurance 0.440, and empathy 0.192. The study concluded that the service quality comprises of all five facotrs of tangibility, reliability, responsiveness, assurance and empathy influencing the patient satisfaction, with assurance as the most influential factor.